2007
DOI: 10.1111/j.1526-4637.2006.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Prescription Drug Diversion Among Drug-Involved Club- and Street-Based Populations

Abstract: While doctor shoppers, physicians and the Internet receive much of the attention regarding diversion, the data reported in this paper suggest that there are numerous active street markets involving patients, Medicaid recipients and pharmacies as well. In addition, there are other data which suggest that the contributions of residential burglaries, pharmacy robberies and thefts, and "sneak thefts" to the diversion problem may be understated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
263
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(275 citation statements)
references
References 42 publications
7
263
0
5
Order By: Relevance
“…They described it as 'disorganized' because there are so many different players involved in the phenomenon, including physicians, pharmacists and other healthcare professionals; drug abusers, patients, students, street dealers and white collar criminals; and tourists, saloonkeepers and all types of service personnel, to name but a few. Federal agencies maintain that the diverted drugs enter the illegal market primarily through 'doctor shoppers', inappropriate prescribing practices by physicians and improper dispensing by pharmacists [132]. Incidardi et al in a study of the mechanisms of prescription drug diversion among druginvolved club-and street-based populations, concluded that while doctor shoppers and the internet receive much of the attention regarding diversion, the data showed there are numerous active street markets involving patients, Medicaid recipients and pharmacists as well [132].…”
Section: Drug Diversionmentioning
confidence: 99%
See 3 more Smart Citations
“…They described it as 'disorganized' because there are so many different players involved in the phenomenon, including physicians, pharmacists and other healthcare professionals; drug abusers, patients, students, street dealers and white collar criminals; and tourists, saloonkeepers and all types of service personnel, to name but a few. Federal agencies maintain that the diverted drugs enter the illegal market primarily through 'doctor shoppers', inappropriate prescribing practices by physicians and improper dispensing by pharmacists [132]. Incidardi et al in a study of the mechanisms of prescription drug diversion among druginvolved club-and street-based populations, concluded that while doctor shoppers and the internet receive much of the attention regarding diversion, the data showed there are numerous active street markets involving patients, Medicaid recipients and pharmacists as well [132].…”
Section: Drug Diversionmentioning
confidence: 99%
“…However, it has been shown that the majority of the drugs come from a single physician's prescription and that family members share it [18]. Inciardi et al described diversion as a disorganized for-profit industry [132]. They described it as 'disorganized' because there are so many different players involved in the phenomenon, including physicians, pharmacists and other healthcare professionals; drug abusers, patients, students, street dealers and white collar criminals; and tourists, saloonkeepers and all types of service personnel, to name but a few.…”
Section: Drug Diversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sale, theft, and forgery of either prescriptions or Drug Enforcement Agency (DEA) numbers are known components of drug diversion [3].…”
Section: Definitionsmentioning
confidence: 99%